2017
DOI: 10.1016/j.bbamcr.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of caveolin-1 in low shear stress-induced breast cancer cell motility and adhesion: Roles of FAK/Src and ROCK/p-MLC pathways

Abstract: Tumor cells translocating to distant sites are subjected to hemodynamic shear forces during their passage in the blood vessels. Low shear stress (LSS) plays a critical role in the regulation of various aspects of tumor cells functions, including motility and adhesion. Beyond its structural role, caveolin-1 (Cav-1), the important component of caveolae, represents a modulator of several cancer-associated functions as tumor progression and metastasis. However, the role of Cav-1 in regulating tumor cells response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…Breast cancer cells have been shown to alter their expression and behavior contingent on specialized cues originating from the surrounding microenvironment. For instance, it has been demonstrated that breast cancer cells show increased invasiveness when cultured in 3D versus 2D substrates (Sung et al, ; Weigelt et al, ) and promote motility, adhesion, and metastasis under shear stress (Avraham‐Chakim et al, ; Avvisato et al, ; Mitchell & King, ; ; Swartz & Lund, ; Xiong et al, ). Cancer cells within primary tumors, pleural effusions, secondary metastasis, and the TME experience a wide range of shear stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer cells have been shown to alter their expression and behavior contingent on specialized cues originating from the surrounding microenvironment. For instance, it has been demonstrated that breast cancer cells show increased invasiveness when cultured in 3D versus 2D substrates (Sung et al, ; Weigelt et al, ) and promote motility, adhesion, and metastasis under shear stress (Avraham‐Chakim et al, ; Avvisato et al, ; Mitchell & King, ; ; Swartz & Lund, ; Xiong et al, ). Cancer cells within primary tumors, pleural effusions, secondary metastasis, and the TME experience a wide range of shear stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In non‐small cell lung cancer cells, SFRP1 is believed to mediate tumor proliferation, invasion, and migration . Downregulation of CAV1 in gastric cancers is reported to correlate with poor prognosis . CXCL14 prevents cell proliferation and promotes apoptosis by targeting chemokines, resulting in the reduction of many solid tumors .…”
Section: Discussionmentioning
confidence: 99%
“…29,[49][50][51] However, only a few published studies have investigated shear stress stimulation of ovarian cancer cells in 2D or 3D culture models. To answer the question of how fluid flow induced wall shear stress affects the cytoskeleton of ovarian cancer and regulates its penetration and spread to the peritoneum, Avraham-Chakim et al fabricated a custom-made 2D shear stress device 45 [shown in Fig.…”
Section: B Shear Stress Models Specific To Ovarian Cancermentioning
confidence: 99%
“…57 For a review of shear stress studies on cancer, the readers are kindly referred to Mitchell and King. 57 Work on breast cancer has shown shear stress to affect: adherence to the endothelium 58 due to an increase in the expression of EMT characteristics, 51 acidic microenvironment development, 59 cancer stem cell populations, 60 migration, 61,62 involvement of caveolin-1 through the FAK/Src, ROCK/pMLC, 52 and PI3K/Akt/mTOR 63 pathways, and glycoprotein IIb/IIIa and avb3 integrin in PI3K/Akt and NF-kB signaling. 64 Glioma cells exposed to shear stress showed migratory activity dependent on matrix metalloproteinase (MMP) activation and expression, 65 while prostate cancer cells showed YAP1 dependent motility.…”
Section: Alternative Shear Bioreactors For Examining Ovarian Cancementioning
confidence: 99%